2021
DOI: 10.1021/acssuschemeng.0c07714
|View full text |Cite
|
Sign up to set email alerts
|

Improved Rheology, Crystallization, and Mechanical Performance of PLA/mPCL Blends Prepared by Electron-Induced Reactive Processing

Abstract: Biodegradable polylactide/modified polycaprolactone (PLA/mPCL) blends were successfully prepared by sustainable electron-induced reactive processing (EIReP) without introducing any chemical compatibilizers. The effects of EIReP modification and mPCL content on the properties of PLA/mPCL blends were comprehensively examined and analyzed. The dynamic rheology test showed that the complex viscosity and storage modulus of the EIReP-modified PLA/mPCL blends increased significantly, implying an improved melt strengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 41 publications
1
26
0
Order By: Relevance
“…It was demonstrated that the incorporation of ionic groups in high molecular weight PLA makes it more amenable to processing applications. Huang et al 194 improved the rheological and mechanical properties by electron-induced reactive processing (EIReP) for improving interfacial energy between immiscible polymer phases without using any compatibilizers. It was observed that the chemical free approach increased the elasticity and melt strength of PLA blends.…”
Section: Processabilitymentioning
confidence: 99%
“…It was demonstrated that the incorporation of ionic groups in high molecular weight PLA makes it more amenable to processing applications. Huang et al 194 improved the rheological and mechanical properties by electron-induced reactive processing (EIReP) for improving interfacial energy between immiscible polymer phases without using any compatibilizers. It was observed that the chemical free approach increased the elasticity and melt strength of PLA blends.…”
Section: Processabilitymentioning
confidence: 99%
“…The blending of PLA with nanofillers was found a most investigated method with excellent results and processability in recent years. [52][53][54][55]…”
Section: Introductionmentioning
confidence: 99%
“…where ΔH m is the melt enthalpy observed from the corresponding heating process of DSC measurement, ΔH cc is the cold crystallization enthalpy, ΔH 0 f is the melting enthalpy of PLA with 100% crystallinity (93.6 J g À1 ), 19 w is the PLA mass ratio.…”
Section: Differential Scanning Calorimeter (Dsc)mentioning
confidence: 99%